Study on the Destructive Effect of Small Faults on Coal Pore Structure. (3rd October 2022) - Liu, Jianbao; Song, Zhimin; Li, Bing; Ren, Jiangang; Chen, Feng; Xiao, Ming; Yang, Chengtao
Abstract : Small fault area in coal mine has great risk of coal and gas outburst. However, the damage effect of small faults on coal pore structure still lacks systematic research. Taking a small reverse fault under Pingmei No. 2 mine as an example, this paper collects the hanging wall coal samples within 5 m from the fault plane and the coal samples 50 m from the fault plane, where there is no fault development. The pore structure characteristics of the two coal samples were analyzed and compared by means of a scanning electron microscope, mercury injection, liquid nitrogen adsorption, and Raman spectroscopy. The test results show that compared with the coal samples without faults, the coal samples at faults form micron-scale fracture zones with constant spacing, stable occurrence, and flat two walls. The pore volume and pore specific surface area of different pore sizes increase, the pore peak of mesopore (100~1000 nm) shifts from 1000 nm to 200~400 nm, and its connectivity is enhanced. The number of micropores (<10 nm) increased significantly, and the ink bottle type pores developed. Faulting also has a certain impact on the macromolecular structure of coal, which shows that the D peak area decreases and the area of G peak increases, indicating that the order degree of macromolecular structure of coal increases.